مقاصد الشريعة في الأموال ووسائلها عند الإمام محمد الطاهر ابن عاشور = The shari'ah goals pertaining to economic wealth and their means in Imam Mohammad al-Tahir Ibn Ashur’s Work - Ahmad, Shabir Ahmad Molavi; El-Mesawi, Mohamed El-Tahir (IIUM Press, 2016)
Sheikh Muhammad al-Tahir Ibn Ashur occupies a prominent place among the scholars who took special interest in the study of goals of Islamic Shari'ah,Maqasid al-Shari'ah, both with regard to their theoretical foundations and ramifi-cations. He was the first in modern times to call for the development of the study of the Shariah goals into an inde-pendent discipline. His reflections of the crucial areas of human transactions to delineate the goals of the Shariah rules pertaining to them is unprecedented by earlier works on Maqasid al-Shari'ah and almost unmatched by Maqasid studies after him, especially in respect of the Shari'ah injunctions concerning financial and economic transactions. Seen the rapidly growing movement of Islamic banking and finance over the last four to five decades, bringing into view Ibn Ashur’s contribution to the elaboration of the Shari'ah goals in wealth and property transactions thereunto can enrich the Islamic economic thought oncomitant with that movement which has taken over international dimensions going far beyond the traditional geographical boundaries of the abode of Islam. Hence, the present article focuses on tracing out Ibn Ashur’s views in this connection and pre-senting them in a systematic way in order to put them at the reach of researchers in Islamic economic thought that seems to have stagnated over the last few years. Key words: Maqasid al-Shari'ah, financial and economic transactions, Islamic economic thought, Ibn Ashur..